2016
DOI: 10.5430/jnep.v6n10p71
|View full text |Cite
|
Sign up to set email alerts
|

A guide for dermatology nurses to assist in the early detection of skin cancer

Abstract: Early diagnosis of skin cancer, particularly melanoma, leads to improved morbidity and mortality. While nurses have been leaders in skin cancer awareness and education for decades, the nursing community can take a more active role in the fight against skin cancer. In order to assume this role, nurses must be familiar with diagnostic aids that help in the early recognition of skin cancer. Dermatology nurses facilitate care in the interdisciplinary team by focusing on patient centered outcomes. Nursing roles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…More than half of the participants in the present study stated that they considered themselves at risk for skin cancer. In several studies conducted on the issue, it has been reported that an individual's perception of risk affects his/her health behavior, medical decision-making and acquisition of health information (23)(24)(25)(26) . In the current study, although more than half of the participants considered themselves at risk of skin cancer, the rate of those who visited a dermatologist was low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than half of the participants in the present study stated that they considered themselves at risk for skin cancer. In several studies conducted on the issue, it has been reported that an individual's perception of risk affects his/her health behavior, medical decision-making and acquisition of health information (23)(24)(25)(26) . In the current study, although more than half of the participants considered themselves at risk of skin cancer, the rate of those who visited a dermatologist was low.…”
Section: Discussionmentioning
confidence: 99%
“…Primary care providers should appreciate the importance of gathering a detailed patient history to identify patients with the highest risk of developing skin cancer (23)(24) . Awareness of the risks and symptoms of skin cancers and of the ways to prevent skin cancer play an important role in avoiding behaviors posing risks in the development of cancer and in taking the necessary precautions (23) . Accordingly, the importance of providing information and raising awareness about skin cancer whose incidence is on the rise becomes more evident.…”
Section: Discussionmentioning
confidence: 99%
“…With increased patient volumes and advanced nursing roles in force (e.g. skin surveillance, lymph node checks, skin protection and self-examination education) (Skripnik Lucas et al, 2016), reviewing and attending to individual patient healthcare needs had to be limited to priority needs only and concluded within a short time space. It is thus important to identify ways to either bring the intervention down to a delivery schedule that is more manageable for lone providers or ensure that adequate resources for nursing support are available.…”
Section: Discussionmentioning
confidence: 99%